Les territoires de marge de la Syrie mandataire : le mouvement autonomiste de la Haute Jazîra, paradoxes et ambiguïtés d’une intégration « nationale » inachevée (1936-1939) - Jordi Tejel Gorgas (Revue des Mondes Musulmans et de la Méditerranée)
At the very beginning of the French Mandate in the Levant, Upper Jazira was a territory of margins, subjected to foreign covetousness as well as to French political and economical projects. However, in 1936, the clauses of the Franco-Syrian Treaty and the victory of the National Bloc at the legislative elections changed the whole picture due to the emergence of a local political movement. While the French officers were instrumental in the creation of the autonomist movement in Jazira, the latter was also a response to the unionist aspirations of a Syrian state in search of “national” foundations.Paradoxically, the emergence of the first autonomist demands led to the “syrianisation” of the political life in Upper Jazira. This article sheds a light on two parallel dynamics. On one hand, urban actors in Upper Jazira reproduced to a certain extent the same “repertoires of action” than in other Syrian cities. On the other hand, and for the first time, the fate of Upper Jazira began a subject of debate among Syrian nationalists so that Upper Jazira started to be integrated into the Syrian national imaginary.